Clinical implications of a positive prostate cancer screen in patients undergoing cardiac transplant evaluation - Kumar, Vaibhav. (2018)
Abstract: Background: Screening the general population for prostate cancer with prostate specific antigen (PSA) testing continues to be controversial. Patients with advanced heart failure undergoing evaluation for cardiac transplantation are often requested to undergo prostate cancer screening, with guiding evidence generated from the general population. The clinical implications of a positive prostate cancer screening result in this patient population has not been determined. Methods: A retrospective cohort study was performed on all men that were referred to a cardiac transplant center between January, 2000 and December, 2015. Patients were classified as having either a 'positive screen' (PSA ≥ 4ng/ml) or a 'negative screen' (PSA < 4ng/ml) at the point of initial evaluation. The primary outcome of time to listing for cardiac transplant (days) was calculated from the date of referral to the date of listing. A multivariable Cox proportional hazards model was developed to assess the association between a positive prostate cancer screening result and listing for cardiac transplantation. For patients with a positive PSA screen individual chart review was performed to ascertain the subsequent diagnostic evaluation and identify patients with a diagnosis of prostate cancer. Results: Among the 704 patients included in our analysis, 66 men (9.4%) had a positive prostate cancer screening result. Men with a positive prostate cancer screen were approximately 4 years older (58.5 ± 8.7 years vs 54.1 ± 11.2 years), more likely to have a diagnosis of ischemic cardiomyopathy (74% vs 53%) and to be on mechanical support at the point of transplant evaluation (61% vs 16%). After adjusting for age, renal function, clinical status at evaluation, history of COPD and the year of evaluation, patients with a positive prostate cancer screen had a 42% reduced likelihood for progressing to cardiac transplant listing compared to those with a negative screen (HR 0.58, 95%CI 0.38-0.91). 4 patients with a positive prostate cancer screen had a confirmed diagnosis of prostate cancer during the evaluation process, representing a positive predictive value of PSA screening of 6.1% and cancer detection rate of 0.6%. Conclusion: Serum PSA performs poorly as a screening modality for prostate cancer in men undergoing a cardiac transplant evaluation, especially in those who are acutely unwell at the point of evaluation. Patients with a positive screen have more adverse clinical characteristics in addition to a reduced likelihood for progressing to listing for cardiac transplant. Given the unique nature of the decision to perform prostate cancer screening in this population, an individualized approach in particular with regards to timing of PSA screening should be encouraged.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Kent.; Committee: David DeNofrio, and Jason Nelson.; Keyword: Epidemiology.